Pengaruh Pendidikan Kewirausahaan dan Locus of Control Internal terhadap Sikap Berwirausaha Mahasiswa - Dwi Sarwo Ningtiyas; Mintasih Indriayu; Jonet Ariyanto Nugroho (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2022)
The pupose of the research is to determine the effect of entrepreneurship education and internal locus of control on entrepreneurial attitudes of students at Sebelas Maret University Surakarta, Class of 2017. 100 of the students were the sample, sampling using proportional random sampling. Data processing using SPSS 23.0 with data Multiple Regression Linear  Analysis analysis techniques. The results of this research show that (1) there was influence a positive and significant impact between entrepreneurship education on entrepreneurial attitudes students at Sebelas Maret University with the t count (2,651) > the t table (1,661). (2) there was influence a positive and significant between internal locus of control on the entrepreneurial attitudes students at Sebelas Maret University with the t count (7,337) > t table (1,661). (3) there was influence a positive and significant influence between entrepreunership education and internal locus of control on the entrepreneurial attitude students at Sebelas Maret University with the F count value (60,802) > F table (3,089). And Value of detemination coefficient analysis (R2) shows a result of 0.547 or 54.7%, meaning that 54.7% of entrepreneurial attitudes are influenced by entrepreneurship education and internal locus of control.